2014
DOI: 10.1097/mpa.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Endoscopic Ultrasound in the Evaluation of Cystic Pancreatic Neoplasms

Abstract: Endoscopic ultrasound is a valuable diagnostic modality in the evaluation of cystic pancreatic neoplasms in a community hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…In our evaluation, the ability of pathologists and cytologists using EUS-FNA samples to detect IPMN showed a sensitivity of 59%, which was lower than that for PDAC (80%), but is consistent with current literature for sensitivity of detecting cystic lesions from 47% to 87% [12,15] . We found our reported specificity (100%) is consistent with other studies that report specificity between 87%-100% [12][13][14][15] . The majority of misdiagnoses that were finally diagnosed as IPMN were suggestive of other benign diagnoses (15/18).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our evaluation, the ability of pathologists and cytologists using EUS-FNA samples to detect IPMN showed a sensitivity of 59%, which was lower than that for PDAC (80%), but is consistent with current literature for sensitivity of detecting cystic lesions from 47% to 87% [12,15] . We found our reported specificity (100%) is consistent with other studies that report specificity between 87%-100% [12][13][14][15] . The majority of misdiagnoses that were finally diagnosed as IPMN were suggestive of other benign diagnoses (15/18).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have only separately evaluated the efficiency of EUS-FNA for diagnosing neuroendocrine tumors [9][10][11] , cystic neoplasms, such as intraductal papillary mucinous neoplasms (IPMN) [12][13][14][15] , or PDAC [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, review of these so‐called negative specimens indicated that there were no diagnostic cells on the smears; therefore, they were considered to be sampling errors. In fact, inadequate sampling has been advocated as one of the main reasons for false‐negative or nondiagnostic samples, especially in cystic lesions . Although beyond the scope of the current report, the wide use of ancillary studies, such as molecular analysis and immunohistochemistry, also has a deep impact on the diagnostic accuracy of cytology, and an emphasis on the use of these ancillary techniques is proposed by the new Papanicolaou Society guidelines .…”
Section: Discussionmentioning
confidence: 96%
“…EUS‐FNA also appeared to be highly effective in patients who underwent a previous nondiagnostic biopsy by other methods and those who had neoplasms other than ductal adenocarcinoma. Several additional factors can also influence the diagnostic yield of EUS‐FNA pancreatic samples, such as the presence of pancreatitis, experience of the endoscopist, use of rapid on‐site assessment, needle size, and clinical characteristics of the lesion (such as cystic vs solid neoplasms) . In addition, cytologic pitfalls, such as atypia caused by inflammatory/reactive changes and scant material coupled with lack of pathologist's or clinician's experience, are main contributors to occasionally reported low sensitivity and false‐negative cases .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that the preoperative diagnostic accuracy for specific cyst type ranged from 47% to 68% compared to surgical pathology [55,56] ; accuracy improved to 73% when cysts were categorized as benign, premalignant and malignant [56] . A retrospective study of 118 patients in a community setting suggested a higher accuracy for EUS (87%) in distinguishing benign, premalignant, and malignant cysts; however, this study is limited because 65% of patients were diagnosed mainly by CT radiologic surveillance with a median follow-up of only 337 d [57] . Therefore, in light of the limitations of current diagnostic tools, novel diagnostic biomarkers have received considerable interest [58] .…”
Section: Eus-fnamentioning
confidence: 92%